How Cannabinol Is Utilized in Japan, a Country with Strict Cannabis Regulations—Its Purposes, Medical Effects, Adverse Events, and Dependence - Yuji Masataka; Futaba Umemura; Akihiko Nagamine; Naoko Miki; Yoshiyuki Akahoshi; Toshihiko Matsumoto; Ichiro Takumi (Integrative Medicine Reports)
Introduction: Cannabinol (CBN) was discovered in 1896, but its commercial use did not take off until recently, and there have been few studies on its use, safety, and efficacy. Japan has strict regulations on cannabis, but CBN products have been legally distributed since late 2020. It is possible to speculate that these products are used for different purposes than in places such as some states of the United States where cannabis is legal, but no academic research has been conducted to date. Objective: To conduct a quantitative evaluation of the use, self-assessed efficacy, dependence, and adverse events of CBN products in Japan. Methods: An online questionnaire was created for CBN users, and a request for responses was disseminated via social networking service. Results: In total, 515 valid responses were obtained. Regarding the purpose of use, 174 (33.8%) were medical, 136 (26.4%) were recreational, and 199 (38.6%) were both. The most common medical purposes were sleeping disorder (N = 325), anxiety (N = 186), and depression (N = 181). Statistically significant subjective symptom improvement was observed before and after CBN use for sleeping disorder, anxiety, and chronic pain. In addition, 82.7% of users reported improved physical quality of life (QOL), 84.1% reported improved mental QOL, and 55.4% reported improved social QOL. The rate of adverse events experienced was 9.9%, and 5.2% were classified as substance use disorders. Conclusions: CBN is used in Japan primarily for self-mental-health care applications, not on a prescription basis, and contributes to improved QOL. The experience rate of adverse events was 10%, the severity was mild, and the dependence was considered milder than that of cannabis.